PENGARUH PENERAPAN PENDEKATAN PENGAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATA PELAJARAN EKONOMI DI SMAN 1 AROSBAYA - Adellia Wijayanti; Ruski Ruski (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of implementing the Project Based Learning (PjBL) approach on students' problem-solving abilities in Economics subjects at SMAN 1 Arosbaya. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The population of this study consisted of all students at SMAN 1 Arosbaya, while the sample comprised two groups selected through cluster random sampling, namely the experimental class and the control class, with a total of 30 students. Data were collected through observation, documentation, questionnaires, and interviews. The collected data were analyzed using validity tests, reliability tests, normality tests, t-tests, and coefficient of determination tests. The results of the study indicate that the implementation of Project Based Learning has a positive and significant effect on students' problem-solving abilities. This finding is supported by the t-test results, which showed a significance value of 0.000 (< 0.05), indicating that the alternative hypothesis was accepted. Therefore, the more effectively Project Based Learning is implemented in Economics learning, the higher the students' problem-solving abilities at SMAN 1 Arosbaya.